Assessment of gingival bleeding after chlorhexidine rinses with or without mechanical oral hygiene - Fouad H Mahmoud; Abdulmajeed H Al-Ani; Dhia K Abbas
The aim of the present study is to investigate the effect of chemical plaque control and/or mechanical plaque control on the gingival bleeding. 20 students volunteers participating in this study from the college of dentistry, have 549 teeth and 2196 teeth surface. The students brushed the teeth in either the left or right side of their mouth twice daily during a 7 days period. After each brushing the rinsed for one minute with 10ml of 0.2% aqueous solution of chlorhexidine digulconate solution. The gingival bleeding tendency was found to decrease on the brushed side and to increase on the side which was only rinsed. Gingival bleeding occurred 63% more frequently than at baseline on the side of only chemical cleaning of 0.2% chlorhexidine. 39% reduction in the gingival bleeding tendency after the use of the combination of the 2 hygiene mechanical and chemical method was noticed.